CHRONIC OBSTRUCTIVE PULMONARY DISEASE AND ALLERGIC BRONCHITIS: MORPHOLOGICAL CHANGES IN BIOLOGICAL FLUIDS (International Educators Conference, 2025)
Chronic obstructive pulmonary disease and allergic bronchitis are among the pressing issues in the global healthcare system. Scientific literature widely highlights that in these diseases, significant morphological changes are observed not only in the bronchial tissues but also in biological fluids. In particular, structural alterations recorded in saliva, blood, and other biological environments are considered important markers in the diagnosis and monitoring of these diseases. A review of the literature shows that the integrated use of saliva crystallization and other fluid markers holds great scientific and practical significance in improving the diagnosis of chronic obstructive pulmonary disease and allergic bronchitis.